PENGARUH AUDITOR SWITCHING DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BEI TAHUN 2019-2021 - DINA MADELINA PRATIWI PUSPITASARI; LORINA SIREGAR SUDJIMAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The purposeiof this study is to analyze the influence of Auditor Switching and Audit Opinions oniAudit Report Lag. The data in this study uses secondaryidata in the form of an audited annual FinancialStatement from banking companies listed on the Indonesia Stock Exchange in 2019-2021 by taking data accessed through the official IDX website, namely www.idx.co.id. Based on predetermined criteria, the data obtained was 126 total samples consisting of 42 companies in financial statements for 3 years. Analyze the data in this study using Descriptive Statistical Analysis, Correlation Coefficient Test, T Significance Test, Multicholinearity Test, Determination Coefficient Test, and Multiple Linear Regression Analysis. The test results showed that Auditor Switching had no effect on Audit Report Lag, and Audit Opinion had no effect on Audit Report Lag.